Research of the charakteristics of competitive activity of the best freestyle wrestlers of the XXXII Olympic games in Tokyo - Barkov, Y. A. (Physical Culture, 2023)
The analysis of the competitive activity of the champions of the XXXII Olympic Games in Tokyo in freestyle wrestling was carried out to determine the optimal model characteristics. The criteria for evaluating competitive activity are proposed, reflecting the degree of comprehensive preparedness of wrestlers for competitions and their sportsmanship, taking into account which allows you to promptly make the necessary adjustments to the training process of training athletes. The tactical and technical readiness of the strongest freestyle wrestlers was studied based on the analysis of their tactical and technical actions throughout the entire Olympic tournament.